Súil eile – jiný úhel pohledu na svět: Revitalizace jazyka v Irsku - Kollinerová, Martina (Lidé města, 2024)
According to Michael Krauss and other authors dealing with the current state of languages, the Irish language is one of the 90% of languages that are most probably going to irretrievably disappear during the next century. In 2009, Irish government has created and published the official Language Revitalisation Plan for the next 20 years. This plan does not precisely follow theoretical models of language revitalisation, such as is the model of Joshua Fishman, which describe the revitalisation process as a process consisting of successive steps, but is ready to apply more language revitalisation tools simultaneously. Field research in the area of Galway and Connemara Gaeltacht (English and Irish-speaking areas) aims to uncover the real state of the Irish language in the area where English and Irish speakers live together and what can be, according to the participants, done to revive the language. Most of them feel quite optimistic about the language, although several revitalisation efforts are criticised. Almost all of the research participants agree on the opinion that to preserve the language, it is absolutely necessary to support the Gaeltacht areas where Irish is spoken on a daily basis. Another form of support should be aimed at Gaelscoils, immersion primary and secondary schools, as well as to Irish language courses in English speaking schools. These courses, however, still seem to be based on obsolete methods, which is most probably the consequence of previous unsuccessful revitalisation efforts. The last part of the article is dedicated to a somewhat neglected method of revitalisation, to verbal art, and to storytelling in particular.